Status of library automation in Tanzania ' s public universities - Samzugi, Athumani S (University of Dar es Salaam Library Journal, 2016)
This paper examines the current status of library automation in Tanzania ' s public universities. It is based on a study that was conducted from September2014 to June 2015. The paper argues that library automation is not an option but a necessity in this ICT era. In fact, the study established that all eight (8) public university libraries have automated their library functions at different levels. On the sources of funding for library automation it was established that reliance on donor support remained the major source of funding for library automation in Tanzania ' s public university libraries. The study findings also show that there is no universally available dominant library management software among public university libraries in the country. As such, there was an urgent need to come up with standard software among public university libraries to facilitate information sharing and exchange of among these institutions. In addition, barriers to effective library automation ought to be overcome to ensure the sustainability of library automation.